ANALISIS VARIAN SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI PADA PTPN VIII UNIT CIKASUNGKA BOGOR, JAWA BARAT - Beni Hariadi; mahagiyani mahagiyani (Politeknik Ubaya, 2023)
This study aims to investigate and determine how the production cost budget is used to control production costs at PTPN VIII Unit Cikasungka in Bogor Jawa Barat, as well as to analyze and determine what causes the disparity between the budget and the actual realization of unfavorable production costs at PTPN VIII Unit Cikasungka in Bogor, Jawa Barat. This study also compare the company's production cost budget with the actual production costs at the end of the period and analysis of variance on the deviations. The type of research data used in this study is the type of quantitative data. The quantitative data in this study namely production cost data in the Company's Work Plan and Budget and realization at PTPN VIII Unit Cikasungka Bogor, West Java. Data collection techniques in conducting this research are techniques documentation, literature study and observation. The data analysis method used is a descriptive method, namely by thoroughly decrypting the data obtained during the process research. The research methods used in research in PTPN VIII Cikasungka Unit is: analysis of raw material cost variance, direct labor cost of one difference, two difference, and three difference, and factory overhead cost analysis of one difference. The results reveal that the production cost budget, that was used to control production costs at PTPN VIII Unit Cikasungka in Bogor Jawa Barat, was not truly effective.